Smart city frameworks SWOT analysis: a systematic literature review - Portia Mupfumira; Michael Mutingi; Michael Sony (Frontiers in Sustainable Cities)
In the past decade, the concept of “smart cities” has gained popularity as a way to address and manage challenges and complexities in urban areas. Different smart city frameworks have been proposed and the term “framework” has been defined, examined and proposed in various ways, with each interpretation taking a distinct approach. From a different angle, some frameworks highlight how the smart city concept is implemented, while others concentrate on assessing the initiatives’ level of success. An additional collection of frameworks concentrated on the essential elements needed to make up a smart city. This research explicitly analyses frameworks concentrating on fundamental components to identify and suggest essential elements for developing an adaptable, sustainable smart city structure. Using a methodological approach that focused on the core elements of smart city structure, the research comprised of conducting a systematic literature review (SLR), and carrying out an analysis of the strengths, weaknesses, opportunities, and threats (SWOT) of existing frameworks. Based on the area of focus, the analysed frameworks were grouped into four categories: human-centric, techno-centric, integrated human-techno-centric and environmental-focus frameworks for easy SWOT analysis. The findings revealed that cyber-security issues pose threats to all frameworks and there are technological dependency vulnerabilities. This shows that technology is the driver/enabler of achieving smart city status. In addition, with the help of proper governance and effective management, involving citizens is key to releasing the potential for sustainable smart forms. Hence, the authors believe that technology, good governance, environmental concerns and citizens are essential components of an adaptable, sustainable smart city framework. A framework built on these crucial components is unique because it can be customised to fit any city. Management, infrastructural development and degree of public participation depend on different city configurations.